2015
DOI: 10.1097/eja.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melatonin premedication to prevent emergence agitation after general anaesthesia in children

Abstract: Compared with placebo, melatonin premedication may be effective in preventing emergence agitation in children (GRADE: low). This TSA suggests that further studies are required to confirm the results. Compared with midazolam, high-dose melatonin might have a significant effect in preventing emergence agitation (GRADE: very low). The study protocol was registered in the UMIN Clinical Trials Registry (registration number: UMIN000011841).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 53 publications
1
24
2
Order By: Relevance
“…In each of the 13 MAs, more than 1000 cases were analysed. For sleep latency, pre-operative anxiety, prevention of agitation or risk of breast cancer, ten (32%) of 31 MAs reported effects that were significant at P values less than 0.05 under the random-effects model, and seven (23%) were significant at P values less than 0.001 under the random-effects model [ 31 , 33 , 38 – 41 ]. For eight MAs (25.8%), we were unable to calculate 95% PIs.…”
Section: Resultsmentioning
confidence: 99%
“…In each of the 13 MAs, more than 1000 cases were analysed. For sleep latency, pre-operative anxiety, prevention of agitation or risk of breast cancer, ten (32%) of 31 MAs reported effects that were significant at P values less than 0.05 under the random-effects model, and seven (23%) were significant at P values less than 0.001 under the random-effects model [ 31 , 33 , 38 – 41 ]. For eight MAs (25.8%), we were unable to calculate 95% PIs.…”
Section: Resultsmentioning
confidence: 99%
“…The patients in the placebo group received the same amount of syrup alone. We determined the dose of ramelteon according to the previous meta-analysis regarding melatonin 9 , which showed that premedication with 0.1-0.5 mg kg −1 of melatonin may effectively prevent emergence agitation 9 . Because ramelteon is a melatonin receptor agonist with higher affinity than that of melatonin itself 10,11 , 0.1 mg kg −1 was considered adequate for the present study.…”
Section: Randomisation and Interventionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Statistical analysis. According to a previous study conducted at our hospital 23 and the previous metaanalysis regarding melatonin 9 , we assumed an emergence agitation incidence of 67% and 21% for the placebo and ramelteon groups, respectively. To enable the detection of differences, we set an alpha error of 0.05 and a statistical power of 0.80.…”
Section: Randomisation and Interventionmentioning
confidence: 99%
“…Although the risk of false-positive results from meta-analyses has been estimated to be as high as 35–50% [ 10 , 11 ], it can be reduced by using a Trial Sequential Analysis (TSA) [ 12 ]. Therefore, we consider TSA an essential tool for meta-analysis [ 13 ], and we used TSA to minimize the high risk of false-positive results.…”
Section: Introductionmentioning
confidence: 99%